The Impact of Applying Individually Perturbed Parametrization Tendency Scheme on the Simulated El Niño-Southern Oscillation in the Community Earth System Model - Wu, Tianjie; Zhang, Shushi; Zhu, Kefeng; Ma, Hongyun (Frontiers in Earth Science, 2021)
The Ensemble technique is considered to be an effective approach to enhancing the model capacity of intra-seasonal climate change. Since El Niño-Southern Oscillation is one of the critical modes of interannual variability in the tropical Pacific, an appropriate ensemble technique may help minimize model bias in ENSO forecast. This research includes a modified stochastically perturbed parameterization tendencies scheme in the Community Earth System Model to investigate its impact on ENSO prediction. This revised scheme using independent noise patterns to perturbs the tendencies from different physical parameterizations. Whereas in the original scheme, only the same noise is employed. The result suggests that the altered approach is in a position to further reduce sea surface temperatures, gain more skill in uncertainty estimation compared to the original one. ENSO's amplitude is improved especially of its warm phase El Niño, but there is a limited improvement in its spatial structure. The modified scheme also ameliorated the variability of ENSO by increasing the magnitude toward observation. The power spectrum exhibits an increased representation. Besides those findings, we notice that simple ensemble mean may not be able to represent the climate status as it smoothes out some useful signals.